(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fairness creams have become a vital product for the Indian FMCG companies. Their overall sales increased due to the importance given by Indian consumers towards fairness creams. As it is known that India is a country popularly known for its diversity and different consumers from different parts of the country prefer different brands. Hence, this paper aims to identify to study the brand preference towards fairness cream among women of rural areas. This paper also examines the factors influencing women of rural areas in preferring various brands of fairness creams. The data was collected in Lucknow city of Uttar Pradesh, India among 150 survey respondents.